Opções metodológicas para o estudo de fenômenos variáveis relacionados à 1a pessoa do discurso - Rubio, Cássio Florêncio [UNESP]; Gonçalves, Sebastião Carlos Leite [UNESP] (My University, 2010)
This paper presents methodology for an integrated treatment of three variable phenomena in Brazilian portuguese: (i) encoding of first-person plural into the forms nós (we) and a gente (the people), (ii) verbal agreement with the pronoun nós and (iii) verbal agreement with the pronominal form a gente. Based on the theoretical framework provided by Labovian sociolinguistics (LABOV, 1966, 1972), the methodology is applied to a sample of Brazilian portuguese spoken in the countryside of São Paulo State (GONÇALVES, 2007). The results indicate that distinct factors predominate in the choice of the alternative forms of each phenomenon: in the verbal agreement with a gente, linguistic factors are the most prominent; in the verbal agreement with nós, social factors are the most salient; and in the use of nós/a gente both linguistic and social factors prevail.

Neste trabalho, apresentamos metodologia para o tratamento conjunto de três fenômenos variáveis do português brasileiro: (i) codificação de primeira pessoa do discurso no plural pelas formas nós e a gente, (ii) concordância verbal com o pronome nós e (iii) concordância verbal com a forma pronominal a gente. Amparada teoricamente na Sociolinguística laboviana (LABOV, 1966, 1972), a metodologia é aplicada a amostras do português falado no interior paulista (GONÇALVES, 2007). Os resultados apontam que fatores de natureza distinta prevalecem na escolha das formas alternantes de cada fenômeno: na concordância verbal com a gente, prevalecem fatores linguísticos; na concordância verbal com nós, fatores sociais, e no uso de nós/a gente, tanto fatores linguísticos quanto sociais.
Keywords: concordância verbal; primeira pessoa do plural; a gente; verbal agreement; first person; nós (we); a gente (the people)